High affinity targeting of CD23 inhibits IgE synthesis in human B cells. Issue 4 (14th July 2015) - Fellmann, Marc; Buschor, Patrick; Röthlisberger, Silvan; Zellweger, Fabian; Vogel, Monique
Abstract: The low‐affinity IgE receptor FcϵRII (CD23) is part of the regulatory system controlling IgE synthesis in human B cells and exists in membrane and soluble forms. Binding of IgE to CD23 has been described to have stabilizing effects and to prevent cleavage of CD23. Previous experiments using anti‐CD23 antibodies reduced IgE synthesis but were difficult to interpret as the antibody Fc part might also mediate feedback mechanisms. The purpose of this study was to investigate the regulatory role of CD23, by using designed ankyrin repeat proteins (DARPins) that specifically recognize CD23. Anti‐CD23 DARPins were isolated by ribosome display and were produced as monovalent and bivalent constructs. Affinities to CD23 were measured by surface plasmon resonance. IgE synthesis and up‐regulation of CD23 in human peripheral B cells were induced by IL‐4 and anti‐CD40 antibody. We assessed CD23 expression and its stabilization by FACS and used an ELISA for detecting soluble CD23. IgE synthesis was measured by ELISA and real‐time PCR. Surface plasmon resonance revealed affinities of the DARPins to CD23 in the pico‐molar range. Anti‐CD23 DARPins strongly inhibited binding of IgE to CD23 and share thus a similar binding epitope as IgE. The DARPins stabilized membrane CD23 and reduced IgE synthesis in an isotype specific manner. Furthermore, the anti‐CD23 DARPins decreased IgE transcript through inhibition of mature Cϵ RNA synthesis suggesting a posttranscriptional control mechanism. This study demonstrates that targeting CD23 alone is sufficient to inhibit IgE synthesis and suggests that a negative signaling occurs directly through the CD23 molecule. Abstract : High affinity DARPin molecules were selected that recognize specifically human CD23. Targeting B cells resulted in a stabilization of membrane CD23 and reduced IgE synthesis in an isotype‐specific manner.